Imaging the main molecular biological subtypes of breast cancer: comparison of mammographic data and histological findings - O. S. Khodorovich; L. B. Kanakhina; T. V. Sherstneva; A. A. Kalinina-Masri; Sh. M. Dibirova (Опухоли женской репродуктивной системы)
Background. Breast cancer (BC) stands as one of the most prevalent malignancies affecting women, posing a significant threat to health and life. Timely diagnosis and treatment of BC play a pivotal role in enhancing patient survival rates.Aim. To explore such a method of visualization of BC as mammography and the correlation of its results with the data of histological and immunohistochemical studies, and their significance in planning organ-conserving operations.Materials and methods. The study involved 217 patients diagnosed with nodular BC (T1-2N1M0). AH patients underwent digital mammography, histological examination of biopsy and surgical specimens, and immunohistochemical analysis of tumor tissue (determination of the expression of sex hormone receptors (estrogen and progesterone), HER2/neu status and the status of the Ki-67 marker, reflecting the proliferative activity of tumor cells).Results. Comparison of mammographic and histological/immunohistochemical findings revealed significant differences in tumor visualization among major molecular subtypes of BC. A statistically significant association (p <0.001) was established between carcinoma in situ and radiological features such as spiculated margins and calcifications on mammography.Conclusion. Mammography emerges as an objective and accessible visualization method for BC, enabling assessment of tumor size and peritumoral region. However, for planning breast-conserving surgery for luminal and HER2-positive BC subtypes, a multimodal diagnostic approach is recommended to assess tumor spread, incorporating ultrasound and contrast-enhanced magnetic resonance imaging.